Deculturalisation Trajectory of the South African Early Childhood Development Centres: Parents’ voices. - Dayile, N, Skota; Mkhomi, Moses Sipho (Universitas Negeri Semarang, 2024)
Traditionally, family sociocultural values are core to child caring and raring, crucial and necessary for children's cognitive growth and learning. This qualitative study sought views of parents on the sociocultural development of their 0 - 4 year old children.